Sharia Marketing Management Strategy in the Online Buying and Selling Mechanism - Cici’ Wilantini; Uly Mabruroh Halida (Universitas Muhammadiyah Sidoarjo, 2022)
The growth of users of online buying and selling transactions continues to increase every year. In online buying and selling transactions, there are many frauds or discrepancies between the contract agreed at the beginning and the goods/services received. The role of sharia marketing management is needed here so that unwanted things do not happen. This research is a library research (Library Research). The references used in this research are books, journals and publications indexed on Google that are still relevant to the research topic. The results of this study indicate that Islamic marketing management is indispensable in the online buying and selling mechanism. Sharia marketing management is the first step to build consumer loyalty by considering product suitability, financial benefits, and spiritual values ​​that are believed to be. The three basic concepts in Islamic marketing management are; strategies for sharing thoughts, tactics for market share, and values ​​for hearts. Then there are five characteristics of Islamic marketing management including; love consumers, honest and transparent as a brand, segmentation a la prophet, keep promises, and maintain the balance of nature. The impact that will be felt on online buying and selling that implements sharia marketing management, namely; consumers will conduct transactions regularly, make purchases with a more diverse range of products, consumers recommend to other potential customers, and the attitude of commitment from consumers to continue to make transactions at the same place.